Selective flocculation-flotation of ultrafine hematite from clay minerals under asynchronous flocculation regulation - Fusheng Niu; Yuying Chen; Jinxia Zhang; Fei Liu; Ziye Wang (International Journal of Mining Science and Technology)
The clay mineral flocculation encapsulation poses a major technical challenge in the field of fine mineral separation. Enhancing the ability to separate clay minerals from target mineral surfaces is key to addressing this issue. In the flotation process of ultrafine hematite, sodium polyacrylate (PAAS) was used as a selective flocculant for hematite, polyaluminum chloride (PAC) as a flocculant for kaolinite and chlorite, and sodium oleate (NaOL) as the collector to achieve asynchronous flocculation flotation. This study examines the flotation separation performance and validates it through experiments on actual mineral samples. The results indicate that with PAAS and PAC dosages of 1.25 and 50 mg·L−1, respectively, the iron grade and recovery of the actual mineral samples increased by 9.39% and 7.97%. Through Zeta potential, XPS analysis, infrared spectroscopy, and total organic carbon (TOC) testing, the study reveals the microscopic interaction mechanisms of different flocculants with minerals, providing insights for the clean and efficient utilization of ultrafine mineral resources.